Class Position, Political Clientelism, and Opinion Formation in Brebes Regency - Alfin Hidayat (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2026)
This study examines how class position shapes the experience and meaning of political clientelism and how these experiences form political opinion in the context of the 2024 local election in Brebes, Indonesia. It explores how different social classes interpret clientelistic practices and how these interpretations influence political attitudes. Using a qualitative case study approach, the research draws on in-depth interviews and thematic analysis of narratives from informal workers, farmers, fishers, lower middle-class citizens, and political brokers in areas where patronage is prevalent. The findings show that clientelism is not merely a transactional exchange but a socially embedded practice rooted in class-based vulnerabilities and moral relations. Labourers view political gifts as survival strategies that foster pragmatic attitudes. Farmers and fishers interpret assistance through reciprocal moral logics that generate obligation. Lower middle-class citizens express ambivalence as democratic ideals confront social pressures. Brokers personalise politics by framing assistance as care. The study concludes that political opinion in Brebes is shaped less by programmes or ideology than by classed experiences and personalised exchanges, and argues that strengthening universal social protection and institutional presence beyond election periods is essential to reduce dependence on clientelistic relations and improve local democracy